Clinical evaluation of porous hydroxyapatite bone graft (Periobone G) with and without collagen membrane (Periocol) in the treatment of bilateral grade II furcation defects in mandibular first permanent molars - Sruthy Prathap; Shashikanth Hegde; Rajesh Kashyap; M S Prathap; M S Arunkumar (Wolters Kluwer Medknow Publications, 2013)
Background: Furcation invasions represent one of the most demanding therapeutic challenges in periodontics. This investigation assessed and compared the clinical efficacy of hydroxyapatite bone graft material when used alone and with collagen membrane in the treatment of grade II furcation defects. Materials and Methods: Ten patients with comparable bilateral furcation defects in relation to mandibular first molars were selected and treated in a split-mouth design. After the hygiene phase of therapy was completed, the groups were selected randomly either for treatment with hydroxyapatite bone graft (Periobone G) alone or with a combination of bone graft and guided tissue regeneration (GTR) membrane (Periocol). Clinical parameters like plaque index, gingival index, vertical probing depth, horizontal probing depth, clinical attachment level, position of marginal gingiva, and the amount of bone fill were used at baseline and at 3 and 6 months postoperatively. Results: At 6 months, both surgical procedures resulted in statistically significant reduction in vertical and horizontal probing depths and gain in the clinical attachment level. Conclusion: The use of combination technique yielded superior results compared to sites treated with bone graft alone. However, the difference was not statistically significant.